Tabelas de vida de fertilidade de Brevicoryne brassicae (L.) (Hemiptera: Aphididae) em condições de campo - Cividanes, Francisco J. [UNESP] (My University, 2002)
Studies related with life tables are fundamental for the understanding of the population dynamics of insects. In this work, Brevicoryne brassicae (L.) was studied during spring, summer, fall and winter through age-specific life tables aiming to evaluate the influence of temperature on its population dynamic. The experiments were carried out observing B. brassicae enclosed in leaf cages fixed in kale, Brassica oleracea L. var. acephala DC. The age-specific life table parameters, computed on a degree-day time scale, indicated that B. brassicae showed the longest survival during the thermal conditions of fall and winter, while its highest fecundity was observed when the aphids experienced spring temperatures. High summer temperatures adversely affected the population dynamic of B. brassicae through its negative influence on immature development, survival, longevity and reproduction.
Age-specific life tables of Brevicoryne brassicae (L.) (Hemiptera: Aphididae) under field conditions
Keywords: Aphid; Brassica oleracea; Degree-day; Population dynamics